2010
DOI: 10.1007/s10933-010-9463-z
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric techniques allow environmental reconstructions from low-diversity continental ostracode assemblages

Abstract: Quantification of intra-specific morphological variability of aquatic biota along environmental gradients can produce biological proxies that can be applied to paleoenvironmental reconstructions. This morphology-derived proxy information can be especially valuable when dealing with low-diversity fossil assemblages, i.e. in situations when paleoenvironmental inference based on species composition of the assemblage is less effective. We analyzed valve size and outline shape of the widespread and highly environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…8 and 9). These results, negative correlation between valve length and solute concentrations, are agree with the relation described to E. virens, Cyprideis torosa (Jones, 1850), Mytilocypris henricae (Chapman, 1966), L. inopinata and some euryhaline ostracods (Barker, 1963;Martens, 1985;Yin et al, 1999;Fernandes Martins et al, 2009;Van der Meeren et al, 2010).…”
Section: Size Variability and Environmental Effectssupporting
confidence: 86%
See 3 more Smart Citations
“…8 and 9). These results, negative correlation between valve length and solute concentrations, are agree with the relation described to E. virens, Cyprideis torosa (Jones, 1850), Mytilocypris henricae (Chapman, 1966), L. inopinata and some euryhaline ostracods (Barker, 1963;Martens, 1985;Yin et al, 1999;Fernandes Martins et al, 2009;Van der Meeren et al, 2010).…”
Section: Size Variability and Environmental Effectssupporting
confidence: 86%
“…E. virens and L. inopinata) that might be explained by genetic and environmental factors (Baltana´s and Geiger, 1998). Van der Meeren et al (2010) observed that a greater shape variance of L. inopinata inhabiting highly fluctuating environments, responds to temperature, specific conductance and higher clonal diversity of populations. It would be interesting to conduct genetic studies of E. fontana to evaluate the genetic variability within and between populations from different sites.…”
Section: Shape Variability and Environmental Effectsmentioning
confidence: 93%
See 2 more Smart Citations
“…Within freshwater invertebrates, ecophenotypic response has been documented for a variety of species, both recent and fossil (e.g., Hellberg et al, 2001;Zieritz and Aldridge, 2009;Inoue et al, 2013;Neubauer et al, 2013;Clewing et al, 2015). 10 Ostracods represent a model group for the study of ecophenotypical variation in response to environmental change (Anadón et al, 2002;Frenzel et al, 2012;Fürstenberg et al, 2015;van der Meeren et al, 2010). Due to their calcitic valves, they have an excellent fossil record and are utilized as palaeoenvironmental and biostratigraphic indicators (Anadón et al, 2002).…”
Section: Introductionmentioning
confidence: 99%